The mangosteen genome - Midin, Mohd Razik; Goh, Hoe-Han (Springer Nature Switzerland, 2022)
Mangosteen is one of the most popular tropical fruits in Southeast Asia. It is called ‘The Queen of Tropical Fruits’ as its thick sepals collectively resemble a crown. Mangosteen fruits contain white and juicy edible pulp with a sweet ﬂavour and pleasant aroma. They are rich in beneﬁcial phytochemicals such as xanthones, which make mangosteen a potential medicinal plant. Traditionally, mangosteen has been used to treat fever, diarrhoea, and wounds. In recent studies, researchers found that mangosteen has anti-cancer and anti-diabetic properties. However, mangosteen is still an underutilised crop due to its slow growth rate with a long juvenile period that usually takes eight to ten years to bear fruit. It is also an obligative apomict with asexual reproduction, hence producing clones of progenies with low genetic variations. Therefore, the breeding programme of mangosteen is challenging with a very low success rate. Furthermore,genetic information on mangosteen accessions in different countries is limited to unravel its lineage and parental history. Other constraints in mangosteen improvement include low viability of recalcitrant seeds and the lack of a rapid propagation method. Efforts have been made to understand this crop through functional genomic studies. Recent genomic studies of mangosteen, including genome sequencing, genome survey, genome size estimation, and cytogenetic analysis, are highlighted in this chapter.